Kemampuan Pemecahan Masalah Matematis: Systematic Literarur Review Tentang Indikator, Tujuan Pembelajaran Dan Kesalahan Siswa - Hizmi Wardani; Izwita Dewi; KMA Fauzi (ANARGYA: Jurnal Ilmiah Pendidikan Matematika, 2026)
Mathematical problem-solving ability is a very important, but in fact, this ability is still relatively low. This study aims to analyze the indicators of mathematical problem-solving ability, identify learning objectives developed to improve problem-solving ability, and examine the types of student errors in solving mathematical problems. The methodology used is a Systematic Literature Review (SLR) using the PRISMA guide.. Data collection techniques were carried out through searching and documenting scientific articles using the Publish or Perish application together with the Google Scholar database from 2016 to 2025. Data were analyzed using content analysis techniques and bibliometric analysis through inclusion and exclusion criteria to map research trends, ability indicators, learning objectives and student errors in mathematical problem solving. Of the 147 articles identified, 28 articles met the inclusion criteria for analysis. The results of the study show that the most dominant Polya indicator is used, namely 71.4%, the learning objectives emphasize conceptual mastery and the development of high-level thinking skills, while the most frequent student errors occur in the re-examination phase (58-75%) which indicates low student metacognition. This review provides an overview of research trends in mathematical problem-solving abilities over the past 10 years and provides practical recommendations for the development of holistic and integrative mathematics learning